Not Virtual Enough: A Virtual Library’s Challenges During the COVID-19 Pandemic - Askin, Nicole; Babb, Maureen; Darling, Pamela; Dingwall, Orvie; Finlay, Lenore; Finlayson, Kathy; Haas, Cheryl; Osterreicher, Angela (Partnership, 2021)
As part of the University of Manitoba Libraries Outreach Services, the Winnipeg Regional Health Authority (WRHA) Virtual Library provides library services to hospitals, health centres, community health agencies, and personal care homes throughout the city of Winnipeg, Manitoba. All services of the WRHA Virtual Library, including the collection, are entirely virtual, though staff are physically located in the University’s health library. In March 2020, shortly after the World Health Organization declared the novel coronavirus disease (COVID-19) pandemic, libraries around the world started closing their doors and staff were required to work from home. The virtual infrastructure of our services and collections required no changes in how our patrons accessed the Virtual Library and a smooth transition was expected, but the sudden shift to working from home revealed gaps. This article discusses the unique experience of the WRHA Virtual Library transitioning to a completely virtual environment, the previous reliance on the University’s physical infrastructure, and the inequities identified between librarians and library technicians.